2022
DOI: 10.1073/pnas.2200991119
|View full text |Cite
|
Sign up to set email alerts
|

Sprayed water microdroplets containing dissolved pyridine spontaneously generate pyridyl anions

Abstract: Significance Water microdroplets can accelerate chemical reactions by orders of magnitude compared to the same reactions in bulk water and/or trigger spontaneous reactions that do not occur in bulk solution. Among the properties of water microdroplets, the unique redox ability resulting from the spontaneous dissociation of OH − into a released electron and •OH at the air–water interfaces is especially intriguing. At the air–water interface, OH − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
92
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…This mechanism might account for the large increase in H 2 O 2 concentration when the N 2 nebulizing gas is replaced by air (which contains 21% O 2 ) or pure O 2 . Many mysteries about the chemical characteristics of water microdroplets remain to be explored and understood, but it does seem clear that water microdroplets can exhibit remarkable reduction powers, such as the reduction of doubly charged ethyl viologen (EV +2 ) to EV +1 and the recent report of the formation of pyridine anions and ·OH when a solution of pyridine dissolved in water was sprayed without the application of any external electric field …”
supporting
confidence: 71%
“…This mechanism might account for the large increase in H 2 O 2 concentration when the N 2 nebulizing gas is replaced by air (which contains 21% O 2 ) or pure O 2 . Many mysteries about the chemical characteristics of water microdroplets remain to be explored and understood, but it does seem clear that water microdroplets can exhibit remarkable reduction powers, such as the reduction of doubly charged ethyl viologen (EV +2 ) to EV +1 and the recent report of the formation of pyridine anions and ·OH when a solution of pyridine dissolved in water was sprayed without the application of any external electric field …”
supporting
confidence: 71%
“…We were motivated to make this study when previous work showed that pyridine (C 5 H 5 N) was able to capture CO 2 . 13 A simple sonic spray setup is sufficient to conduct this CO 2 /FA conversion in the Tz/water microdroplets (Figure 1).…”
mentioning
confidence: 99%
“…Microdroplet, an emerging class of chemical reactor, has attracted significant interests for chemical reactions acceleration by several orders of magnitude (10–10 6 ), probably because of the special air-water interface physicochemical properties ( Enami et al., 2014 ; Wei et al., 2020 ; Yan, 2021 ). In previous studies, the electrospray mass spectrometer is frequently employed for microdroplets generation, reaction and analysis ( Mehrgardi et al., 2022 ; Müller et al., 2012 ; Zhao et al., 2022 ). However, it is important to investigate the microdroplet chemistry at an individual droplet level to understand the mechanisms.…”
Section: Before You Beginmentioning
confidence: 99%